Ecological Restoration of the Boreal Forest in Fennoscandia - Hjältén, Joakim; Kouki, Jari; Tolvanen, Anne; Sjögren, Jörgen; Versluijs, Martijn
Mixed-severity disturbances have historically shaped boreal forests, creating a dynamic mosaic landscape. In Fennoscandia, however, intensive even-aged forest management has simplified the forest landscape, threatening biodiversity. To safeguard this biodiversity, we therefore need to restore structural complexity in hitherto managed forests. Knowledge generated from relevant case studies on natural disturbance emulation–based ecological restoration suggests that prescribed burning positively affects many early-successional organisms. Gap cutting benefits some insects and wood fungi but has a limited effect on birds, bryophytes, and vascular plants. Restoration of deciduous forests appears to benefit light- and deciduous tree–associated insect species and some forest birds. 2023